Structure of the yellow fever NS5 protein reveals conserved drug targets shared among flaviviruses - Dubánková, Anna; Boura, Evzen (Antiviral research, 2019)
Yellow fever virus (YFV) is responsible for devastating outbreaks of Yellow fever (YF) in humans and is associated with high mortality rates. Recent large epidemics and epizootics and exponential increases in the numbers of YF cases in humans and non-human primates highlight the increasing threat YFV poses, despite the availability of an effective YFV vaccine. YFV is the first human virus discovered, but the structures of several of the viral proteins remain poorly understood. Here we report the structure of the full-length NS5 protein, a key enzyme for the replication of flaviviruses that contains both a methyltransferase domain and an RNA dependent RNA polymerase domain, at 3.1 Å resolution. The viral polymerase adopts right-hand fold, demonstrating the similarities of the Yellow fever, Dengue and Zika polymerases. Together this data suggests NS5 as a prime and ideal target for the design of pan-flavivirus inhibitors.
Keywords: Models, Molecular; Yellow Fever; replikace viru; proteinové domény; zvířata; Disease Outbreaks; methyltransferasy; Yellow Fever Vaccine; Binding Sites; RNA-dependentní RNA-polymerasa; Protein Conformation; vazebná místa; RNA-Dependent RNA Polymerase; Primates; Virus Replication; virus žluté zimnice; konformace proteinů; Drug Design; žlutá zimnice; Viral Nonstructural Proteins; Zika Virus Infection; molekulární modely; Yellow fever virus; zinek; Dengue; primáti; infekce virem zika; vakcína proti žluté zimnici; epidemický výskyt choroby; Animals; virové nestrukturální proteiny; Methyltransferases; Zinc; racionální návrh léčiv; dengue; Protein Domains